Pleiotropic antifibrotic actions of aspirin-triggered resolvin D1 in the lungs - Guilherme, Rafael F.; Silva, José Bruno N.F.; Waclawiack, Ingrid; Fraga-Junior, Vanderlei S.; Nogueira, Thaís O.; Pecli, Cyntia; Araújo-Silva, Carlla A.; Magalhães, Nathalia S.; Lemos, Felipe S.; Bulant, Carlos A.; Blanco, Pablo J.; Serra, Rafaela; et al. (Frontiers in Immunology, 2023)
Pulmonary fibrosis is a destructive, progressive disease that dramatically reduces life quality of patients, ultimately leading to death. Therapeutic regimens for pulmonary fibrosis have shown limited benefits, hence justifying efforts to evaluate the outcome of alternative treatments. Using a mouse model of bleomycin (BLM)-induced lung fibrosis, in the current work we asked whether treatment with pro-resolution molecules, such as pro-resolving lipid mediators (SPMs) could ameliorate pulmonary fibrosis. To this end, we injected aspirin-triggered resolvin D1 (ATRvD1; i.v.) 7 and 10 days after BLM (intratracheal) challenge. Two weeks later, assessment of pathogenic outcome in the lung tissues revealed that ATRvD1 partially restored lung architecture, reduced leukocyte infiltration, and inhibited formation of interstitial edema. In addition, lung tissues from BLM-induced mice treated with ATRvD1 displayed reduced levels of TNF-𝛼, MCP-1, IL-1-𝛽, and TGF-𝛽. Of further interest, ATRvD1 decreased lung tissue expression of MMP-9, without affecting TIMP-1. Highlighting the beneficial effects of ATRvD1, we found reduced deposition of collagen and fibronectin in the lung tissues. Congruent with the anti-fibrotic effects that ATRvD1 exerted in lung tissues, 𝛼-SMA expression was decreased, suggesting that myofibroblast differentiation was inhibited by ATRvD1. Turning to culture systems, we next showed that ATRvD1 impaired TGF-𝛽-induced fibroblast proliferation and differentiation into myofibroblast. After showing that ATRvD1 hampered microparticle release in the supernatants from TGF-𝛽-stimulated cultures of mouse macrophages, we verified that ATRvd1 also inhibited the release of microparticles in the bronco-alveolar lavage (BAL) fluid of BLM-induced mice. Motivated by studies showing that BLM-induced lung fibrosis is linked to angiogenesis, we asked whether ATRvD1 could blunt BLM-induced angiogenesis in the hamster cheek pouch model (HCP). Indeed, our intravital microscopy studies confirmed that ATRvD1 abrogates BLM-induced angiogenesis. Collectively, our findings suggest that treatment of pulmonary fibrosis patients with ATRvD1 deserves to be explored as a therapeutic option in the clinical setting.